Issues of the Modern Constitutional Process: The Moral Foundations of Public Authority (in the Aspect of Legal Guarantees of Democracy) - TOMKINA, Olena O.; YAKOVLIEV, Andrii A. (Journal of Advanced Research in Law and Economics; Vol 9 No 7 (2018): JARLE Volume IX Issue 7(37) Winter 2018, 2019)
Since mid-2015, the constitutional process has intensified in Ukraine, which has begun the work of the new Constitutional Commission. At present, constitutional reform is ongoing in Ukraine, which is being implemented in three priority areas, which include ‘point changes’ to the Constitution of Ukraine. The purpose of the article is to analyze the relationship of moral principles of organization and implementation of state power with the realization of democracy. The moral and legal aspect of the newest stage of the constitutional democratic development of Ukrainian statehood, in particular, in the context of European integration of Ukraine, is analyzed. The crucial role of the constitutional and legal provision of morality in the activity of the state for the constitutional development of Ukraine is substantiated. The relationship between the principle of integrity of the public service and the constitutional foundations of the people's power is determined. The importance of constitutional and legal consolidation of the requirements of public integrity for the establishment in Ukraine and its development as a rule of law has been proven.